Aspectos perturbativos das Teorias com a quebra da simetria de Lorentz - Silva, Antônio José Gomes Carvalho (2017)
In this dissertation, we study the possibility of violation of the Lorentz invariance taking into account some terms of the standard extended model, more specifically, the part of this model that deals with the extended quantum electrodynamics. We perform quantum corrections in the fermionic sector of the usual quantum electrodynamics added with terms that violate the Lorentz symmetries and in two different configurations. First, the coefficient added and that causes the Lorentz symmetry breaking is introduced through the constant pseudo-tensor Ic juvAp And we treat the constant electric and magnetic fields, that is, we do not evaluate as external leg between the coupling of the photon and fermions, evaluating the field FAp Without opening in term of the gauge field. In the second case, we investigated the operators governed by the coefficient of interaction FAp open in term of the gauge field. In the second case, we investigated the mixed contribution of the minimum and non-minimum coupling. We immediately know that for each coupling evaluated will have their respective vertices. For both cases, we calculate the quantum corrections in a loop. In the first case, the theory with the coefficient Ic juvAp and field FAp without being opened at the end of the gauge field AP, The contribution of a loop and we calculate the counter-ter, having a CPT-par characteristic, which will be useful to be introduced in action to eliminate divergences. In the second case, we examined the contribution of a loop, considering the mixture of minimum and non-minimum coupling, that is, and and and an external one AP, having a CPT-par characteristic, One related to the non-minimum coupling and another to the minimum, respectively and verifying the vertex correction also having the contribution of its counter-term.